Possible Protective Effect of Low Dose of Papaverine on ANIT Induce Cholestasis in Rat - Adnan Atshan, Doaa; Munaf H. Zalzala (Iraqi Journal of Pharmaceutical Sciences, 2023)
AbstractIntrahepatic cholestasis is clinical syndrome which cause either by defect in synthesis or bile acid flow, the pathophysiology of cholestasis is complicated by a number of variables, including oxidative stress, inflammatory response, and dysregulation of bile acid transporter . Rats, mice, and guinea pigs were utilized as experimental animals, and ANIT was administered to them in order to create a model that closely resembled intrahepatic cholestasis in human. This study examined the protective effects of papaverine, a non-narcotic opium alkaloid derived from papaver somniferum and discovered as an FXR agonist, on cholestasis in rats induced by alpha-naphthylisothiocyanate (ANIT). Rats utilized in this study divided into 3 groups (10 rats per each groups), group I (control) or vehicle group rat administered corn oil (1ml/kg) once daily 48 hour before sacrifice group II rats orally administered alpha-naphthylisothiocyanate (ANIT) 100mg/kg single dose 48hour before sacrifice group III rats administered 100mg/kg papaverine orally for 7 consecutive days and at day 5 rat administered alpha-naphthylisothiocyanate (ANIT) The results showed that papaverine treatment decreased alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), total bilirubin, total bile acid, as well as increased antioxidant enzyme GPX and decreased MDA and inflammatory mediators tumor necrosis factor TNF- and interleukin IL1-β. In conclusion, papaverine may have a protective effect to alleviate ANIT-induced cholestasis and may be a therapeutic target to treat cholestasis.